2018
DOI: 10.1097/mao.0000000000001695
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Outcome After Cochlear Implantation Is Not Related to Surgical Technique: A Double Blinded, Randomized Clinical Trial of Round Window Approach Versus Cochleostomy

Abstract: Objective:To establish whether the round window approach (RWA) leads to less vestibular dysfunction and dizziness than the standard cochleostomy approach (SCA) during cochlear implant (CI) surgery, as assessed using the video head impulse test (vHIT).Additionally, objective findings were compared with the subjective dizziness perceived by the patient.Study Design:Double blinded, clinical randomized trial.Setting:University Hospital.Patients:Fifty-two ears from 46 patients were included. Inclusion criterion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This percentage is higher than found in the present study (7.7%), but they tested patients on the second day after surgery, which may mainly reflect a very acute change after surgery. In contrast, Korsager et al (2018) showed no difference of mean lateral SCC gain values up to one month postoperatively. Regarding mean lateral SCC VOR gain changes, the meta-analysis of Ibrahim et al that pooled five studies (n ¼ 122 patients) with several methods of HIT execution, including search coils, did not find a mean change after cochlear implantation (Ibrahim et al 2017).…”
Section: Discussionmentioning
confidence: 63%
“…This percentage is higher than found in the present study (7.7%), but they tested patients on the second day after surgery, which may mainly reflect a very acute change after surgery. In contrast, Korsager et al (2018) showed no difference of mean lateral SCC gain values up to one month postoperatively. Regarding mean lateral SCC VOR gain changes, the meta-analysis of Ibrahim et al that pooled five studies (n ¼ 122 patients) with several methods of HIT execution, including search coils, did not find a mean change after cochlear implantation (Ibrahim et al 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Five papers were analyzed for speech perception [ 21 , 27 - 30 ]. Three papers were analyzed for vestibular dysfunction [ 31 - 33 ]. Due to the lack of homogeneity in the data, statistical analyses could not be carried out, and summative data was reported.…”
Section: Reviewmentioning
confidence: 99%
“…Three of the included studies evaluated vestibular dysfunction [ 31 - 33 ]. One study showed that the RW approach resulted in less vestibular dysfunction when compared to the C approach [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study by Korsager et al . 9 indicated that surgical technique has no effect on vestibular function.…”
Section: Introductionmentioning
confidence: 99%